2022
DOI: 10.26911/thejmch.2022.07.04.09
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Lavender Aroma Therapy for Better Quality of Sleep in Pregnant Women: Meta-Analysis

Abstract: Background: Sleep is a state of natural rest for the body that must be fulfilled every day. Sleep patterns of each individual are always different depending on age, lifestyle, environment, activities and health conditions. This study aims to analyze the primary study of the effectiveness of lavender aromatherapy to improve sleep quality in pregnant women with a meta-analysis. Subjects and Method: This study is a systematic review and meta-analysis with PICO as follows Population: pregnant women, Intervention: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…National Sleep Foundation reported 60% og pregnant women complained tiredness and more than 75% of them experienced sleep disturbance (Aswitami et al, 2021). Teha et al showed correlation between decreasing sleep quality and pregnancy in later trimester (Teha et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…National Sleep Foundation reported 60% og pregnant women complained tiredness and more than 75% of them experienced sleep disturbance (Aswitami et al, 2021). Teha et al showed correlation between decreasing sleep quality and pregnancy in later trimester (Teha et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This could lead to tiredness, mental issue such as cognitive disorder, hallucination, illusion, and unstable mood and et cetera (Subandi, 2018dalam (Mu'alimah et al, 2022. Lack of sleep quantity and quality might increase the risk to deliver by cesarean section by 4,5 times and low birth weight baby (Teha et al, 2022). It also leads to hypertension, preeclampsia, and fetal growth delay (Hassan Zaky, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality and quantity of sleep are interrelated and greatly affect the need for sleep. If the quantity of individual sleep is less than it should be, the quality of sleep will also have an effect, and vice versa (Teha et al, 2022).…”
Section: Introductionmentioning
confidence: 99%